Simultaneous Pharmacokinetic Modeling of Alkylresorcinols and Their Main Metabolites Indicates Dual Absorption Mechanisms and Enterohepatic Elimination in Humans. Issue 11 (10th September 2014) - Marklund, Matti; Strömberg, Eric A.; Lærke, Helle N.; Knudsen, Knud E. Bach; Kamal-Eldin, Afaf; Hooker, Andrew C.; Landberg, Rikard
Abstract: Background: Alkylresorcinols have proven to be useful biomarkers of whole-grain wheat and rye intake in many nutritional studies. To improve their utility, more knowledge regarding the fate of alkylresorcinols and their metabolites after consumption is needed. Objective: The objective of this study was to develop a combined pharmacokinetic model for plasma concentrations of alkylresorcinols and their 2 major metabolites, 3, 5-dihydroxybenzoic acid (DHBA) and 3-(3, 5-dihydroxyphenyl)-propanoic acid (DHPPA). Methods: The model was established by using plasma samples collected from 3 women and 2 men after a single dose (120 g) of rye bran and validated against fasting plasma concentrations from 8 women and 7 men with controlled rye bran intake (23, 45, or 90 g/d). Alkylresorcinols in the lymph and plasma of a pig fed a single alkylresorcinol dose (1.3 mmol) were quantified to assess absorption. Human ileostomal effluent and pig bile after high and low alkylresorcinol doses were analyzed to evaluate biliary alkylresorcinol metabolite excretion. Results: The model contained 2 absorption compartments: 1 that transferred alkylresorcinols directly to the systematic circulation and 1 in which a proportion of absorbed alkylresorcinols was metabolized before reaching the systemic circulation. Plasma concentrations of alkylresorcinols and their metabolites depended on absorption and formation, respectively, and the mean ± SEM terminal elimination half-life of alkylresorcinols (1.9 ± 0.59 h), DHPPA (1.5 ± 0.26 h), and DHBA (1.3 ± 0.22 h) did not differ. The model accurately predicted alkylresorcinol and DHBA concentrations after repeated alkylresorcinol intake but DHPPA concentration was overpredicted, possibly because of poorly modeled enterohepatic circulation. During the 8 h following administration, <2% of the alkylresorcinol dose was recovered in the lymph. DHPPA was identified in both human ileostomal effluent and pig bile, indicating availability of DHPPA for absorption and enterohepatic circulation. Conclusion: Intact alkylresorcinols have advantages over DHBA and DHPPA as plasma biomarkers for whole-grain wheat and rye intake because of lower susceptibility to factors other than alkylresorcinol intake.